Capacity Building Madrasah Growing: From Creative Economy to Quality Management of MBS in Islamic Education - Subiyantoro Subiyantoro; Siti Zubaida (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
Increased capacity building for madrasahs needs to be done in order to solve problems and develop the potential of madrasas to improve the quality of madrasas in Kulon Progo Yogyakarta. There are two private Tsanawiyah Madrassas that is almost less in demand by the public even though they are in the middle of an Islamic society. The problem is the strength of the Muslim community's interest in the Tsanawiyah Madrasa and the relation between potential and quality in the Tsanawiyah Madrasa. This study uses descriptive qualitative methods. The purpose of this research is to help solve the problems that occur in the madrasa, as well as develop the potential of madrasas through capacity building in the form of creative economic empowerment, and unravel the problems in terms of quality management. Its data collection techniques are through observation, interviews, and documentation studies. Data retrieval techniques are carried out by snowball sampling techniques. The results of this study are in the form of solving problems with managerial steps carried out by the head of the madrasa. Empirical solutions in the form of strengthening the field of Tahfidz, Batik skills education, waste management into goods of creative economy value, as well as providing assistance with batik skills tools, as well as the pioneering boarding school. This effort is able to increase the existence of the Tsansawiyah madrassa. Empirical solutions in the form of strengthening the field of Tahfidz, Batik skills education, waste management into goods of creative economy value, as well as providing assistance with batik skills tools, as well as the pioneering boarding school. This effort is able to increase the existence of the Tsansawiyah madrassa. Empirical solutions in the form of strengthening the field of Tahfidz, Batik skills education, waste management into goods of creative economy value, as well as providing assistance with batik skills tools, as well as the pioneering boarding school. This effort is able to increase the existence of the Tsansawiyah madrassa.